The Story of Naoufel - Abderrahim El Habachi (L’Année du Maghreb)
This original piece of creative non-fiction, The Story of Naoufel (by El Habachi) explores the challenges faced by a young gay Moroccan struggling to find care and a sense of belonging after being diagnosed with HIV.